If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 5(8 + 9n) = 4(9n + 1) -7x + (8 * 5 + 9n * 5) = 4(9n + 1) -7x + (40 + 45n) = 4(9n + 1) Reorder the terms: 40 + 45n + -7x = 4(9n + 1) Reorder the terms: 40 + 45n + -7x = 4(1 + 9n) 40 + 45n + -7x = (1 * 4 + 9n * 4) 40 + 45n + -7x = (4 + 36n) Solving 40 + 45n + -7x = 4 + 36n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-36n' to each side of the equation. 40 + 45n + -36n + -7x = 4 + 36n + -36n Combine like terms: 45n + -36n = 9n 40 + 9n + -7x = 4 + 36n + -36n Combine like terms: 36n + -36n = 0 40 + 9n + -7x = 4 + 0 40 + 9n + -7x = 4 Add '-40' to each side of the equation. 40 + 9n + -40 + -7x = 4 + -40 Reorder the terms: 40 + -40 + 9n + -7x = 4 + -40 Combine like terms: 40 + -40 = 0 0 + 9n + -7x = 4 + -40 9n + -7x = 4 + -40 Combine like terms: 4 + -40 = -36 9n + -7x = -36 Add '7x' to each side of the equation. 9n + -7x + 7x = -36 + 7x Combine like terms: -7x + 7x = 0 9n + 0 = -36 + 7x 9n = -36 + 7x Divide each side by '9'. n = -4 + 0.7777777778x Simplifying n = -4 + 0.7777777778x
| -(7x+3)-(5x-3)=7-(2x+1) | | 2Y=3X-Y | | 3(-2)-1=-2-5 | | 3x+41=65 | | 12(-2b-12)=-6(-3b+10) | | -2x+1=3x-9 | | -5x=-2x-6 | | 7500x=5900x+88000 | | (x+72)(x+48)=6912 | | -15-32n=4(-8n+4) | | 120-5a+7=8a-16a-35 | | 8y+1=9y-7 | | 4x+89=7x-74 | | 3x+2=3x-3 | | 4h^2=-62h-30 | | 2x/3=15 | | 2x/3-9=32 | | (7x^2-3x-16)+(8x^2+8x)= | | 240x+35=5y+135x | | 3x^3=81 | | 6y=z | | 3(3e+2f)+yf+2=0 | | Y=5/2x+1 | | 4x+3x+5= | | 24+b=40 | | 38-y=250 | | 18+4y=2(3-y) | | c=P+3b+a | | 5/(b+5)-2/b | | 23x^2-15=6x | | 4/x=8/17 | | 9+4y=(3-y) |